2012
DOI: 10.1007/s00330-012-2724-7
|View full text |Cite
|
Sign up to set email alerts
|

A novel functional infrared imaging system coupled with multiparametric computerised analysis for risk assessment of breast cancer

Abstract: • 3D functional infrared imaging (3DIRI) provides new metabolic signatures from breast lesions. • 3DIRI offers high sensitivity for risk assessment of breast cancer. • It also has reasonable specificity. • This initial experience warrants further evaluation in larger clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…This surface separates the datapoints, which belong to distinct classes, from each other with maximum margin. SVMs are popular, because of their high classification accuracy even under adverse conditions, such as nonlinear and high dimensional datasets and very few cases for training the model [66,67]. If the data is nonlinear, the boundary problems, encountered by the SVM, are nonlinear as well [68,69].…”
Section: Support Vector Machine (Svm)mentioning
confidence: 99%
See 2 more Smart Citations
“…This surface separates the datapoints, which belong to distinct classes, from each other with maximum margin. SVMs are popular, because of their high classification accuracy even under adverse conditions, such as nonlinear and high dimensional datasets and very few cases for training the model [66,67]. If the data is nonlinear, the boundary problems, encountered by the SVM, are nonlinear as well [68,69].…”
Section: Support Vector Machine (Svm)mentioning
confidence: 99%
“…Receiver Operating Characteristic (ROC) plots provide a pure index of accuracy by demonstrating the limits of a test's ability to discriminate between alternative states of health over the complete spectrum of operating conditions. A wide range of studies on IR thermography used the ROC curve to measure the cutoff point, diagnostic accuracy (indicated by the area under the curve), sensitivity, and specificity [67,89]. Despite these positive characteristics, Cook points out that ROC measures may be mediocre in assessing models that predict future risk or stratify individuals into risk categories [90].…”
Section: Receiver Operating Characteristic (Roc)mentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous proof of concept study, three-dimensional functional infrared imaging (3DIRI) showed high sensitivity in assessing the likelihood of breast cancer [14] and may be a useful addition to the arsenal of tools in breast cancer diagnosis. This method, based on physiology and metabolic changes, is non-invasive, does not involve ionizing radiation, involves no contact with the breasts, and is thought to operate independent of breast density.…”
Section: Introductionmentioning
confidence: 99%
“…Positively, SVM can yield significant accuracy particularly in difficult conditions. This include high dimensional and nonlinear datasets and, little cases to train the model [145,146]. For a nonlinear data, the boundary problem is also nonlinear.…”
Section: Support Vector Machine (Svm)mentioning
confidence: 99%